"Death Becomes Them". A Funeral Home Ethnography - Jackson, Kathy F. (My University, 2009)
Drawing on theoretical frameworks from Religious Studies, Anthropology and Sociology, this dissertation poses the question: How is religious meaning constructed in the face of death in contemporary North America, given that commercial establishments, non-denominational funeral chapels, have become the primary context for the performance of death rituals dealing with death, the dead and the bereaved?
The dissertation is based on an extended period of ethnographic research at the Marlatt Funeral Home in Dundas, Ontario, a corporately owned non-denominational funeral home which serves a very diverse, but predominantly urban religious population. I concentrate on the funeral professionals as well as clergy and the bereaved in their contribution to the cultural construction and social organization of death in contemporary North America.
While there is an extensive body of social science literature on death and funerary practices in non-Western contexts, there is very little systematic academic research on death and funeral practices in contemporary North America, in particular, in Canadian settings. My dissertation furthers the discussion started in studies by Emke (2001) and Small ( 1997) which focus on funeral practices in Newfoundland as well as studies by Bradbury (1999), Davies (2002), Howarth (1996) and Walter (1990, 1994, 1996, 1998) elsewhere in the Anglophone West by focusing on funeral practises in an urban Canadian setting This dissertation demonstrates that funeral directors perform a complicated role as mediators and ritual specialists balancing multiple domains of spirituality, emotion, personal taste, institutionalized religion, ethnicity and commerce. Furthermore, I argue that funeral directors mediate between the living and the dead, between life and death, and between this world and the afterlife, as it is conceived of by their clients.
Keywords: religion, religious, non-denominational funeral chapels, death, ritual